KUALITAS PELAYANAN KESEHATAN PASIEN BPJS DI RUMAH SAKIT ISLAM SITTI MARYAM MANADO - BANDU, SULASTRI; RUMAPEA, PATAR; KOLONDAM, HELLY (Sam Ratulangi University, 2018)
Health care is one of the fundamental rights of societies that are organized by the mandatory Governmentarranged. One important element in the system of hospital is labour, organization and quality of medicalpersonnel and nurses in the hospital, because it will affect the quality of the management and service.Therefore the hospital as a health care provider must provide satisfying service towards patients SocialInsurance Administration Organization (BPJS). Because the hospital is an organization that sells services,then a quality service is one of the demands that must be met. Hence the need for an action that is trulyconcerned with the public interest in terms of providing services that are really good to society. The purposeof this research is to know the patient's medical service quality in hospital BPJS Islam of Sitti MaryamManado. This study uses qualitative methods. Informants in this study amounted to seven people. Datacollection techniques used are interviews, observation and documentation. Measurement using the theory ofParasuraman with five dimensions of service quality that is reliability, empathy, intangibles, responsiveness,assurance. The results of this study stated that by using five dimensions of service quality measurement of thehealth of the patient in hospital BPJS Islam of Sitti Maryam Manado votes is enough. More suggestionsimprove existing facilities and infrastructure at the Islamic Hospital of Sitti Maryam Manado in order tosupport existing services. Hospital employees should mutually enhance the sense of the importance ofhospitality towards the patient or patient's family in the service of process in order for the patient or thepatient's family gave a good response against an employee of the hospital.Keywords: Quality Of Service, Patient BPJS